Sprachenpolitik in Europa – Tatsachen und Perspektiven - Ehlich, Konrad (Stellenbosch Papers in Linguistics Plus, 2012)
This paper characterizes the linguistic situation in Europe in the context of the global language situation. It describes the significance of the "Project Nation" for the European national languages. European unification after World War II is examined in terms of its linguistic consequences in a number of linguistically sensitive areas such as the economy and science. The language-political activities of the European Council and the European Union are characterized. A distinct language concept is necessary for furthering the linguistic development of Europe – such a language concept should take into account the teleological, the gnoseological and the communitary dimension of language in equal measure. I argue against a pseudo-solution for the language question through the propagation of a "lingua franca" and instead plead for a complex linguistic education concept for Europe, in which multilingualism is regarded and language-politically stated as a cultural and intercultural challenge. Central to this concept is the development of a workable hermeneutics. Keywords: Schlüsselbegriffe: Europa, „Projekt Nation“, europäische Vereinigung, Europarat, Europäische Union, „lingua franca“, Mehrsprachigkeit, Interkulturalität, Hermeneutik, teleologische, gnoseologische, kommunitäre Dimension von Sprache Europe, “Project Nation”, European unification, European Council, European Union, “lingua franca”, multilingualism, interculturalism, hermeneutics, teleological, gnoseological, communicatory dimension of language